Biogenic fabrication of ZnO nanoparticles using Trigonella foenum-graecum (Fenugreek) for proficient photocatalytic degradation of methylene blue under UV irradiation - Alshehri, Abdulmohsen Ali; Malik, Maqsood Ahmad (Journal of materials science. Materials in electronics, 2019)
The biosynthesis is an eco-friendly, reliable, sustainable protocol for preparing nanomaterials where use of natural, biodegradable, non-toxic and safe reagents takes place. In the present work, an efficient, facile and eco-friendly approach has been used for the synthesis of zinc oxide nanoparticles (ZnO-NPs) using Trigonella foenum - graecum (Fenugreek) aqueous seed extract as bio-reducing agents and capping agent, thus eradicating the requirement of conventional reducing agents. Different characterization techniques like UV–Vis spectroscopy, UV–Visible diffuse reflectance spectroscopy, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy, photoluminescence (PL) study and energy dispersive X-ray were employed for confirmation of optical properties, shape, size, surface structure, crystalline nature and elemental proportions of the biogenic ZnO-NPs. FTIR analysis confirms the active role of bioactive phytochemical constituents present in the Trigonella foenum - graecum aqueous seed extract. XRD analyses of the as prepared ZnO-NPs are crystalline in nature and have no other impurity phase. UV–Vis spectral data suggested optical band gap energy of 2.97 eV for biosynthesized ZnO-NPs showing their small size owing to quantum confinement. UV–Vis spectra of ZnO-NPs show the characteristic absorption band at 364 nm, which can be assigned to the intrinsic band gap absorption of ZnO-NPs because of the electron transitions from the valence band to the conduction band. In addition, the efficacy of biosynthesized ZnO-NPs to act as highly efficient photocatalyst for methylene blue (MB) dye degradation under UV-light under different experimental conditions was confirmed in this study. The effect of initial dye concentration, ZnO photocatalyst dosage and the reusability tests were investigated. Improved photocatalytic behavior was discussed and influence of active species was further investigated using hydroxyl radical ( ● OH), superoxide anions ( ● O 2 − ) and hole (h + ) scavengers to explain the possible mechanism of the photocatalytic MB dye degradation under UV light irradiation.